Implementation of Augmented Reality to Improve Vocabulary Mastery at Madrasah Tsanawiyah Negeri 2 Makassar - Supardi, Nur Azizah; Syahid, Akhmad; Syahrul, Muhammad; Zainal, Abdul Qahar; Wahab, Abdul (Program Studi Pendidikan Bahasa Arab, Fakultas Agama Islam, Universitas Muslim Indonesia, 2025)
This study investigates the effectiveness of Augmented Reality (AR)-based learning media in improving Mufradat (vocabulary) mastery among 8th-grade students at Madrasah Tsanawiyah Negeri 2 Makassar. Titled